2014
DOI: 10.3402/ljm.v9.23564
|View full text |Cite
|
Sign up to set email alerts
|

Oral health in Libya: addressing the future challenges

Abstract: Libya is a vast country situated in North Africa, having a relatively better functioning economy with a scanty population. This article is the first known attempt to review the current state of oral health care in Libya and to explore the present trends and future challenges. Libyan health system, oral health care, and human resources with the present status of dental education are reviewed comprehensively. A bibliographic study of oral health research and publications has been carried out. The results point t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 27 publications
0
22
0
1
Order By: Relevance
“…Most of the analyzed published articles were affiliated to Benghazi universities which alone have published 29/40 articles (72.5%) whereas other universities in the other cities have only contributed to less to 30% over 10 years period. 8 This study has similarly concluded that Benghazi University (which currently include Al-Arab Medical Sciences and Garyounis University) was the highest publishing institutes, however they mentioned that thier study indicate that Tripoli University and Al Jabal Al Gharbi University scored the second highest productive rate.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Most of the analyzed published articles were affiliated to Benghazi universities which alone have published 29/40 articles (72.5%) whereas other universities in the other cities have only contributed to less to 30% over 10 years period. 8 This study has similarly concluded that Benghazi University (which currently include Al-Arab Medical Sciences and Garyounis University) was the highest publishing institutes, however they mentioned that thier study indicate that Tripoli University and Al Jabal Al Gharbi University scored the second highest productive rate.…”
Section: Discussionmentioning
confidence: 87%
“…[4][5][6][7] Although many studies have investigated and analyzed the biomedical research productivity and trends from Libya, limited information is available on the oral and dentistry field or other professional medical disciplines. 8 Therefore the purpose of this brief study was to investigation the trends of biomedical publications productivity of oral and dentistry field from Libya using the most popular biomedical search engine PubMed with focus on Libyan academic institutions.…”
Section: Introductionmentioning
confidence: 99%
“…Authors reported a number of important consequences arising from the lack of national policy and regulation regarding oral health workforce management including insufficiently skilled or excessively trained personnel, maldistribution of services, unmet oral health needs and unequal access and use of resources . Data about the distribution of dentists are incomplete, and the lack of registration data of dentists and/or other health practitioners is frequently cited .…”
Section: Resultsmentioning
confidence: 99%
“…Situational analyses from different countries reported an ‘explosive growth’ in the number of dental colleges, mainly in urban areas and an increased privatization of dental colleges . The authors expressed concern that this rapid expansion and lack of government oversight could lead to compromises in the quality of the dental education.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation